2014
DOI: 10.1128/mcb.00740-14
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic-Stress-Induced Rearrangement of the 14-3-3ζ Interactome Promotes Autophagy via a ULK1- and AMPK-Regulated 14-3-3ζ Interaction with Phosphorylated Atg9

Abstract: c 14-3-3 promotes cell survival via dynamic interactions with a vast network of binding partners, many of which are involved in stress regulation. We show here that hypoxia (low glucose and oxygen) triggers a rearrangement of the 14-3-3 interactome to favor an interaction with the core autophagy regulator Atg9A. Our data suggest that the localization of mammalian Atg9A to autophagosomes requires phosphorylation on the C terminus of Atg9A at S761, which creates a 14-3-3 docking site. Under basal conditions, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 54 publications
1
69
0
Order By: Relevance
“…AMPKα phosphorylation of ULK1 also controls Atg9a localization (Mack et al, 2012). In fact, the localization of Atg9a to autophagosomes requires ULK1- and AMPK-dependent phosphorylation of this protein (Weerasekara et al, 2014). Despite these advances, precise roles of AIC components in regulating infection remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…AMPKα phosphorylation of ULK1 also controls Atg9a localization (Mack et al, 2012). In fact, the localization of Atg9a to autophagosomes requires ULK1- and AMPK-dependent phosphorylation of this protein (Weerasekara et al, 2014). Despite these advances, precise roles of AIC components in regulating infection remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…machinery when they revealed that the YWHA/14-3-3 docking sites are created by phosphorylation on Ser234 and Ser295 in human BECN1 22 and on Ser761 near the C terminus of mammalian ATG9. 23 These docking sites are also associated with structurally plastic protein domains (Fig. S3).…”
mentioning
confidence: 99%
“…This displacement of cofilin from 14-3-3 clearly involves AMPK because the effect was abolished after silencing of AMPK. Interestingly enough, AMPK has been shown to phosphorylate several 14-3-3 binding partners [56][57][58] consistent with a competitive displacement of cofilin. Free cofilin is not anymore protected from dephosphorylation and can subsequently be dephosphorylated, 59 leading to cofilin activation and, ultimately, actin filament severing.…”
Section: Discussionmentioning
confidence: 99%